Development of an intervention to expedite cancer diagnosis through primary care: a protocol. Issue 3 (2018) - Stanciu, Marian Andrei; Law, Rebecca-Jane; Nafees, Sadia; Hendry, Maggie; Yeo, Seow Tien; Hiscock, Julia; Lewis, Ruth; Edwards, Rhiannon T; Williams, Nefyn H; Brain, Katherine; Brocklehurst, Paul; Carson-Stevens, Andrew; et al.
No abstract available